2019
DOI: 10.4171/jems/914
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mixing and parabolic divergence in smooth area-preserving flows on higher genus surfaces

Abstract: We consider typical area preserving flows on higher genus surfaces and prove that the flow restricted to mixing minimal components is mixing of all orders, thus answering affimatively to Rohlin's multiple mixing question in this context. The main tool is a variation of the Ratner property originally proved by Ratner for the horocycle flow, i.e. the switchable Ratner property introduced by Fayad and Kanigowski for special flows over rotations. This property, which is of independent interest, provides a quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Since R ′ δ 1/3 x δ y , m R ′′ max(k, T ) and we are in Case 2, for R ′′ > 1 large enough we have the following lower bound: c ′ 2 q −1 ζ 1/2 k 1/2 mδ x 10 max(C ′ p −1 k 1/2 δ w , q −1 ζ 3/2 C ′ k 3/2 δ x ) and analogously for (z, w), (z, w ′ ). This gives (18). By the cocycle identity and by Lemma 5.5, there exists κ ′′′ ǫ > 0 such that for κ ∈ (0, κ ′′′ ǫ ), for all u, w ∈ [0, 2ζ(M + L)] with |u − w| κM, we have…”
Section: Now We Can Prove Theoremmentioning
confidence: 84%
See 1 more Smart Citation
“…Since R ′ δ 1/3 x δ y , m R ′′ max(k, T ) and we are in Case 2, for R ′′ > 1 large enough we have the following lower bound: c ′ 2 q −1 ζ 1/2 k 1/2 mδ x 10 max(C ′ p −1 k 1/2 δ w , q −1 ζ 3/2 C ′ k 3/2 δ x ) and analogously for (z, w), (z, w ′ ). This gives (18). By the cocycle identity and by Lemma 5.5, there exists κ ′′′ ǫ > 0 such that for κ ∈ (0, κ ′′′ ǫ ), for all u, w ∈ [0, 2ζ(M + L)] with |u − w| κM, we have…”
Section: Now We Can Prove Theoremmentioning
confidence: 84%
“…Then the authors showed in particular that the SWR-property holds for a full measure set of mixing flows with logarithmic singularities (Arnol'd flows) thereby proving higher order mixing in this class. The result in [5] was strengthened in [18], where the authors showed that the SWR-property holds for a full measure set of Arnol'd flows on surfaces of higher genus.…”
Section: Introductionmentioning
confidence: 95%
“…The first estimate (in Lemma 6.4) provides a fine control of f (r) (of order r log r with optimal control on the constants) as long as one assumes that the points in the orbit of x of length r stay sufficiently far from the singularity. Estimates similar to Lemma 6.4 but in the more general context of interval exchange transformations were proved by the third author in [37] (see Proposition 3.4 in [37], as well as its generalization by Ravotti in [32] and Proposition 4.4 in [21]) and inspired in turn by the work of Kochergin on rotations, see e.g. [24].…”
Section: Estimates Onmentioning
confidence: 92%
“…The set Z is such that the points y, y satisfy a Ratner-type form of shearing either going forward or backward in time (see (7.4)). This is essentially the set on which the switchable Ratner property (see Section 2.5) holds for the Arnold flow and the definition is indeed the same as the set Z is in [10] or [21]. If y, y display this good form of Ratner-like shearing going forward, we then show that the Forward assumptions (F 1) − (F 4) in F. of Proposition 5.1 hold, while if the Ratner-like form of shearing happens backward, we show that the Backward assumptions (B1) − (B4) in B. of Proposition 5.1 hold.…”
Section: Disjointness In Arnol'd Flows (Proof Of Theorem 12)mentioning
confidence: 99%
See 1 more Smart Citation